Clustering Coconut Farmers – A Successful Extension Approach for Enhancing Adoption and Income from Marginal and Small Holdings - P. Anithakumari (International Coconut Community, 2008)
The study was conducted to document the process of cluster approach among the coconut farmers, impact of adoption of integrated practices for root (wilt) affected area, on income, yield and health of palms as well as improvement in intercropping and allied farm enterprises. The results indicated that clustering farmers of contiguous area enables participation and involvement of women, youths and farmers usually not covered under any R&D programmes and better resource management. The scaling up of the cluster model by various extension agencies, resulted in improvement of coconut yield by 90-100% and intercropped area by 2-4 times. The self perpetuating income generating activities among the farmers were vermicomposting/coconut basin management with green manure crops, crop diversification, backyard poultry by the women farmers and farm level coconut value addition among women self help groups.